2000
DOI: 10.1076/phbi.38.6.55.5954
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Investigation Of Mammea Siamensis

Abstract: A new 4-alkylcoumarin, mammea B/AC cyclo D ( 1 ), together with a 4-phenylcoumarin, mammea A/AC cyclo D ( 2 ), were isolated from the hexane extract of the dried flower of Mammea siamensis . Their structures were determined on the basis of spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Its IR and UV data (see Materials and Methods) as well as the 1 H-NMR data are in agreement with those reported [4]. However, the reported 13 C-NMR data [3] are different from our assignments. Based on the information obtained from the COSY-45, HMQC, HMBC spectra, the 1 H and 13 C signals were assigned ( Table 1).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Its IR and UV data (see Materials and Methods) as well as the 1 H-NMR data are in agreement with those reported [4]. However, the reported 13 C-NMR data [3] are different from our assignments. Based on the information obtained from the COSY-45, HMQC, HMBC spectra, the 1 H and 13 C signals were assigned ( Table 1).…”
supporting
confidence: 89%
“…Mammea harmandii (Pierre) Kosterm (Guttiferae) is an evergreen tree found in Vietnam, Laos and Thailand [1]. As part of our continuing search for anticancer agents, the investigation of the cytotoxic EtOAc extract from the leaves and twigs of this unexplored species has led to the isolation of two new naturally occurring Mammea coumarins, isomesuol (mammea A/BD) (1) [2], [3], [4] and mammearin A (2), together with the known mammea A/BA (3) [4], [5], [6], [7] mammea A/BB (4) [4], [5], [6], [7], [8], [9], mammea A/AA cyclo D (mammeigin) (5) [7], [10], [11], [12], mammea A/AB cyclo D (6) [10], [11], [12], mammea A/AD cyclo D (7) [11], [12], mammea B/AC cyclo D (8) [12], [13], mammea B/AD cyclo D (9) [12], mammea E/BC cyclo D (10) [14] and mammea E/BD cyclo D (11) [14]. We now report the details of the isolation and structure elucidation of these coumarins, as well as the cytotoxic activities of the active compounds 1, 3 and 4.…”
mentioning
confidence: 99%
“…The flowers of this plant have traditionally been used as a heart tonic, fever-lowering, and enhancement of appetite in Thailand (Morikawa et al, 2012;Tung et al, 2013;Ninomiya et al, 2016;Sangkaruk et al, 2017). Previous chemical studies on the flowers (Kaweetripob et al, 2000;Prachyawarakorn et al, 2000Prachyawarakorn et al, , 2006aMahidol et al, 2002;Morikawa et al, 2012;Ninomiya et al, 2016), seeds (Laphookhieo et al, 2006(Laphookhieo et al, , 2007, twigs (Poobrasert et al, 1998;Prachyawarakorn et al, 2006a,b), and bark (Ngo et al, 2010) of M. siamensis reported on the isolation of several coumarins and xanthones, etc. With regard to the biological studies on M. siamensis and its constituents, cytotoxicity, antiproliferative, and apoptotic effects against several tumor and cancer cell lines (Ngo et al, 2010;Tung et al, 2013;Noysang et al, 2014;Uto et al, 2016;Sangkaruk et al, 2017), suppressive effects on inducible nitric oxide synthase expression in RAW264.7 cells (Morikawa et al, 2012), and aromatase inhibitory activity (Ninomiya et al, 2016;Tanabe et al, 2017) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers of this plant have been used for preparing a heart tonic in Thai traditional medicine ("Sarapi" in Thai). [1][2][3][4][5][6][7][8][9][10] Several coumarins, [1][2][3][4][5][6][7] xanthones, 8,9) triterpenoids, 10) and steroids 10) have been isolated from the flowers, 1,2,6,7,10) seeds, 3,9) twigs, 4,8) and bark 5) of this plant. In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells.…”
mentioning
confidence: 99%